2006
DOI: 10.1136/oem.2005.025205
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of occupational exposure to styrene and styrene-7,8-oxide in the reinforced plastics industry

Abstract: Objective: To identify demographic and work related factors that predict blood levels of styrene and styrene-7,8-oxide (SO) in the fibreglass reinforced plastics (FRP) industry. Methods: Personal breathing-zone air samples and whole blood samples were collected repeatedly from 328 reinforced plastics workers in the Unuted States between 1996 and 1999. Styrene and its major metabolite SO were measured in these samples. Multivariable linear regression analyses were applied to the subject-specific levels to expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The presence of dichloromethane (arithmetic mean concentration 51 mg/m 3 ) was reported in a study of Danish industries, including reinforced plastics, that used styrene in the period 1955–1988; perchloroethylene and trichloroethylene were also detected in a small number of samples, but the concentrations were very low 28. Styrene 7,8-oxide has been detected more recently in the air of reinforced-plastic manufacturing workshops,30 but no measurements were available for the facilities included in this study. Workers involved in the lamination process may also have been exposed to man-made fibres, including continuous glass filaments; although no data on exposure levels were available for the cohort, previous studies have not demonstrated a link with cancer 31…”
Section: Discussionmentioning
confidence: 87%
“…The presence of dichloromethane (arithmetic mean concentration 51 mg/m 3 ) was reported in a study of Danish industries, including reinforced plastics, that used styrene in the period 1955–1988; perchloroethylene and trichloroethylene were also detected in a small number of samples, but the concentrations were very low 28. Styrene 7,8-oxide has been detected more recently in the air of reinforced-plastic manufacturing workshops,30 but no measurements were available for the facilities included in this study. Workers involved in the lamination process may also have been exposed to man-made fibres, including continuous glass filaments; although no data on exposure levels were available for the cohort, previous studies have not demonstrated a link with cancer 31…”
Section: Discussionmentioning
confidence: 87%
“…Indeed, we observed limited concordance between measured blood styrene and NATA estimated concentrations (Werder EJ, submitted ). In occupational studies, the correlation between styrene in blood and indoor air ranges from 0.62 to 0.94 11,96,98 . In a study of low occupational styrene levels measured in air, blood, and urine, the highest correlations with ambient levels were observed for blood styrene 95 .…”
Section: Discussionmentioning
confidence: 99%
“…A further evaluation of these data showed that the type of product and job title were important predictors of styrene exposure. The job titles "laminator" and "grinder/sander" were associated with higher exposures, as was the production of RVs (Serdar et al 2006).…”
Section: Indoor Airmentioning
confidence: 98%
“…Almost 40 years ago, female workers exposed to averaged styrene concentrations of 50 to over 150 ppm during hand lay-up operations in a fiberglass boat manufacturing plant had end-of-shift blood concentrations of 200 to 1,220 µg/L, depending upon the type of protective equipment used (Brooks et al 1980). End-of-shift blood samples collected from workers at 17 U.S. FRP factories between 1996 and 1999 were lower, ranging from 90 to 330 µg/L (depending on task and respirator use), and were markedly correlated with concentrations in personal air samples (Luderer et al 2004;Serdar et al 2006). Mean blood and personal air styrene concentrations in female workers in this study were 130 µg/L and 11.5 ppm, respectively, while values for male workers were twice as high (270 µg/L and 20.5 ppm, respectively).…”
Section: Frp Industry Workersmentioning
confidence: 99%